Optimal Ranking of Compost Facilities that Can Be Established in Samsun Province by COCOSO and WASPAS Methods - Sinan Dündar; Hüdaverdi Bircan; Hasan Eleroğlu (Turkish Journal of Agriculture: Food Science and Technology)
The compost product, which offers many benefits such as the evaluation of organic wastes, improvement of soil structure, neutralization of toxins and pH balance of the soil, has significant potential for the improvement of our country's lands. Considering the development of animal existence in our country, the production of compost product to be obtained from feces, which is the product of these animal beings, is an issue that needs to be emphasized. The choice of plant location, which must be determined for an investment to be made for the acquisition of this product emerges as a separate problem. For this reason, in this study, the order of optimality among the alternatives for compost plant installation is considered as a multi-criteria decision making problem. For this purpose, the criteria determined for 10 clusters with the potential of 35,829 animals that can produce compost in Samsun were weighted by the SWARA method. The optimal ranking of these 10 compost clusters was carried out using the COCOSO and WASPAS methods, by means of the criteria weights taken into consideration. According to the ranking results obtained from both methods, it was determined that the cluster number 27 was in the first rank, the cluster no 13 was in the second rank, and the cluster no 14 was in the third rank.